The COVID-19 pandemic and physical activity - Woods, Jeffrey A.; Hutchinson, Noah T.; Powers, Scott K.; Roberts, William O.; Gomez-Cabrera, Mari Carmen; Radak, Zsolt; Berkes, Istvan; Boros, Anita; Boldogh, Istvan; Leeuwenburgh, Christiaan; Coelho-Júnior, Hélio José; Marzetti, Emanuele; et al. (Sports medicine and health science, 2020)
The SARS-CoV-2-caused COVID-19 pandemic has resulted in a devastating threat to human society in terms of health, economy, and lifestyle. Although the virus usually first invades and infects the lung and respiratory track tissue, in extreme cases, almost all major organs in the body are now known to be negatively impacted often leading to severe systemic failure in some people. Unfortunately, there is currently no effective treatment for this disease. Pre-existing pathological conditions or comorbidities such as age are a major reason for premature death and increased morbidity and mortality. The immobilization due to hospitalization and bed rest and the physical inactivity due to sustained quarantine and social distancing can downregulate the ability of organs systems to resist to viral infection and increase the risk of damage to the immune, respiratory, cardiovascular, musculoskeletal systems and the brain. The cellular mechanisms and danger of this “second wave” effect of COVID-19 to the human body, along with the effects of aging, proper nutrition, and regular physical activity, are reviewed in this article.